Research on methods of building an interactive map in a web application - Katerynych, L.O.; Sazonov, N.V. (Проблеми програмування, 2022)
The purpose of this article is to formulate a list of rules for creating an efficient and convenient informational system for vicinity and building navigation and to create a web-app with this functionality. To accomplish this, a web-app user experience, navigation data representation options, their user perception and influence on their emotions were analyzed. Also, a list of recommendations for data representation and storing inside the app alongside with ways of fetching them was composed. General navigational application development practices were described in this work, a test version of an application was created to harvest users’ reviews and feedback and a "University interactive map" web-application for classroom, teacher rooms, departments, laboratories information displaying and navigating buildings and vicinities was created. Метою роботи є формулювання правил створення ефективної і зручної інформаційної системи для навігації та створення веб-застосунку з даним функціоналом. Було проаналізовано спосіб використання подібної програми, особливості подання навігаційних даних та їх сприйняття людиною. Також було складено список даних для збереження в інформаційній системі на кожному етапі її роботи для більш зручного використання. У роботі було описано основні практики розробки інформаційної системи для навігації, створено тестову робочу версію для збору відгуків і побажань, а також розроблено програмний продукт «Інтерактивна карта університету» для показу інформації про аудиторії, кабінети викладачів, кафедр, навігації територіями і будівлями університету